Antiviral Effect of Nonfunctionalized Gold Nanoparticles against Herpes Simplex Virus Type-1 (HSV-1) and Possible Contribution of Near-Field Interaction Mechanism - Edyta Paradowska; Mirosława Studzińska; Agnieszka Jabłońska; Valeri Lozovski; Natalia Rusinchuk; Iuliia Mukha; Nadiia Vitiuk; Zbigniew J. Leśnikowski (Molecules, 2021)
The antiviral activity of nonfunctionalized gold nanoparticles (AuNPs) against herpes simplex virus type-1 (HSV-1) in vitro was revealed in this study. We found that AuNPs are capable of reducing the cytopathic effect (CPE) of HSV-1 in Vero cells in a dose- and time-dependent manner when used in pretreatment mode. The demonstrated antiviral activity was within the nontoxic concentration range of AuNPs. Interestingly, we noted that nanoparticles with smaller sizes reduced the CPE of HSV-1 more effectively than larger ones. The observed phenomenon can be tentatively explained by the near-field action of nanoparticles at the virus envelope. These results show that AuNPs can be considered as potential candidates for the treatment of HSV-1 infections.